Biopolitics and Speculative Objects in Chilean Health Projects - Castillo-Sepulveda, J (SAGE Publications Ltd, 2023)
‘Biopolitics’ is a much-used concept in recent academic literature. One of its main fields of application is in the analysis of public health projects. This article analyses the national Explicit Health Guarantees project in Chile from that perspective. However, we criticize the standard invocation of ‘biopolitics’ by observing that such public health projects require technoscientific operations that establish truths and regimes of obligation for the groups involved -understanding regime both as a set of imposed orders and a set of regulated processes. Specifically, the Explicit Health Guarantees project defines what we call ‘speculative objects’. These have two characteristics: (a) They relate highly diverse entities into integrated wholes that are and involve objects of knowledge and uncertainty, and (b) this integration creates regimes of obligation considered as scientific truths on many different groups. We conclude by proposing new questions about the notion of biopolitics and its relationship with uncertainty and speculation. © The Author(s) 2022.
Keywords: biopolitics; public health; speculative objects; uncertainty